Reinforced zirconia ceramics and preparation method and application thereof

By introducing elements such as Zr, Y, Mg, Al and other elements into zirconia ceramics and forming specific subphase, the impact resistance and density of zirconia ceramics are solved, and mechanical properties, dielectric properties, light transmittance and processing properties are achieved. The balanced and suitable for electronic products and other applications.

CN116535223BActive Publication Date: 2025-01-14BYD CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210096014.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-26
Publication Date
2025-01-14
Estimated Expiration
2042-01-26

AI Technical Summary

Technical Problem

In some application scenarios, existing zirconia ceramics are insufficient impact resistance and have high density, and are difficult to meet the requirements of lightweighting, and are difficult to balance mechanical properties, dielectric properties, light transmittance and processing properties.

Method used

By introducing specific elements and subphase, including Zr, Y, Mg, and Al, a solid solution of tetragonal phase zirconia and MgAl12O19 or MgAl2O4 is formed, and prepared by wet grinding method to form a subphase in the whisker form. Improve the impact resistance and processing properties of ceramics.

Benefits of technology

It significantly improves the impact resistance of zirconia ceramics, achieves low density, low dielectric constant, low light transmittance and good processing performance, and meets the performance requirements of electronic product shells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003491028530000261
    Figure BDA0003491028530000261
  • Figure BDA0003491028530000271
    Figure BDA0003491028530000271
  • Figure BDA0003491028530000272
    Figure BDA0003491028530000272
Patent Text Reader

Abstract

The present invention relates to ceramic materials, and discloses a reinforced zirconia ceramic and a preparation method and application thereof. The ceramic comprises, in terms of elements, Zr, Y, Mg, and Al; the physical phase of the ceramic comprises: tetragonal zirconia and a secondary phase, wherein the secondary phase is MgAl 12 O 19 and / or MgAl 2 O 4 The tetragonal zirconium oxide is a solid solution of yttrium oxide and zirconium oxide. The reinforced zirconium oxide ceramic has a dielectric constant of 15-35.5 and a density of no more than 6g / cm 3 , hardness not greater than 1400Hv, transmittance less than 20%, drop hammer height greater than 25cm, thinning speed greater than 28 wires / h, especially strong impact resistance, and has low density, low dielectric constant, low transmittance and good processing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of zirconia ceramics, and in particular to reinforced zirconia ceramics and a preparation method and application thereof. Background Art

[0002] With the widespread application of zirconia materials in 3C electronic products, optical communications, biomedicine, smart wearables and other fields, the requirements for the comprehensive performance of zirconia ceramics are getting higher and higher. In specific application scenarios, the high hardness and high strength advantages of conventional zirconia ceramics can no longer fully meet the use requirements. For example, when used to prepare large-area appearance parts, the impact resistance is weak, and when used to prepare thin electronic product back covers, the semi-transparency is magnified. In addition, the consumer market has increasingly stringent requirements on dielectric constant and density. Developing zirconia ceramic products with excellent comprehensive performance for specific fields is the key to breaking the application bottleneck.

[0003] At present, there are few studies and reports on high impact-resistant zirconia ceramics in this field, which often only focus on indicators such as strength and toughness, and rarely pay attention to mechanical properties, dielectric properties, density, light transmittance and processing performance at the same time.

[0004] CN1170787C discloses a method for preparing a tetragonal zirconium oxide polycrystalline ceramic co-stabilized by magnesium oxide and yttrium oxide. The method mainly focuses on the bending strength and toughness of the prepared (Mg, Y)-TZP ceramic, and does not involve the impact resistance, dielectric properties, density and light transmittance of the product.

[0005] How to achieve a balance among multiple indicators of zirconia ceramic products, including mechanical properties, density, dielectric properties, light transmittance and processability, is of great significance for broadening the application of zirconia and improving its effects. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of existing zirconia ceramics, such as weak impact resistance and high density that make it difficult to meet the requirements of lightweight, as well as the problem of difficulty in taking into account the performance of low density, low dielectric constant, impact resistance, low light transmittance, and processability, and to provide reinforced zirconia ceramics and their preparation method and application.

[0007] In order to achieve the above object, the first aspect of the present invention provides a reinforced zirconia ceramic, wherein the ceramic comprises, in terms of elements, Zr, Y, Mg, and Al; the physical phase of the ceramic comprises: tetragonal zirconia and a secondary phase, wherein the secondary phase is MgAl 12 O 19 and / or MgAl 2 O 4 ; The tetragonal zirconia is a solid solution formed by yttrium oxide and zirconium oxide.

[0008] Preferably, based on the total weight of the ceramic, the ceramic comprises, in terms of elements, 20.65-72.1 wt % of Zr, 0.61-5.45 wt % of Y, 0.0037-11.83 wt % of Mg, and 0.038-34.78 wt % of Al.

[0009] Preferably, when the molar ratio α of Mg to Al satisfies: α=1 / 12, the secondary phase is MgAl 12 O 19 When the molar ratio of Mg to Al satisfies: 1 / 12<α<1 / 2, the secondary phase is MgAl 12 O 19 and MgAl 2 O 4 When the molar ratio of Mg to Al satisfies: α = 1 / 2, the secondary phase is MgAl 2 O 4 .

[0010] Preferably, MgAl 12 O 19 In the ceramic, MgAl 2 O 4 It has a spinel structure.

[0011] Preferably, the MgAl 12 O 19 The aspect ratio of the whiskers is ≥4.

[0012] Preferably, based on the total weight of the ceramic, the physical phase of the ceramic comprises: more than 30 wt % of tetragonal zirconia and less than 70 wt % of a secondary phase.

[0013] Preferably, the dielectric constant of the ceramic is 15-35.5 and the density is not more than 6g / cm 3 , hardness is not greater than 1400Hv, transmittance is less than 20%, drop hammer height is greater than 25cm, and thinning speed is greater than 28 wires / h.

[0014] Preferably, the ceramic comprises: more than 90wt% of tetragonal zirconia, less than 10wt% of secondary phase, and the dielectric constant of the ceramic is 30-35.5; or the ceramic comprises: 70-90wt% of tetragonal zirconia, 10-30wt% of secondary phase, and the dielectric constant of the ceramic is 20-30; or the ceramic comprises: more than 30wt% and less than 70wt% of tetragonal zirconia, more than 30wt% and less than 70wt% of secondary phase, and the dielectric constant of the ceramic is 15-20.

[0015] A second aspect of the present invention provides a method for preparing a reinforced zirconia ceramic, comprising:

[0016] (1) wet-grinding a powder containing magnesium oxide, aluminum oxide and yttria-stabilized zirconium oxide with water, a dispersant and a binder to obtain a slurry;

[0017] (2) drying the slurry to obtain a composite powder;

[0018] (3) forming and sintering the composite powder in sequence to obtain ceramics;

[0019] The molar ratio of magnesium oxide to aluminum oxide in the powder is γ, and 1 / 6≤γ≤1.

[0020] The third aspect of the present invention provides a reinforced zirconia ceramic prepared by the preparation method described in the second aspect.

[0021] A fourth aspect of the present invention provides an electronic product housing, wherein the electronic product housing comprises the reinforced zirconia ceramic described in the first aspect or the third aspect.

[0022] Through the above technical solution, the reinforced zirconia ceramic provided by the present invention contains a specific element composition, and the zirconia phase is doped with a secondary phase with a specific composition and content, and the secondary phase is MgAl in the form of whiskers. 12 O 19 , or MgAl with spinel structure 2 O 4 , or MgAl in whisker form 12 O 19 MgAl with spinel structure 2 O 4 The coexistence of the two mixtures can significantly enhance zirconia, so that the enhanced zirconia ceramic has high impact resistance, and at the same time has low density, low dielectric constant, low light transmittance and good processing performance. In addition, the preparation method of the present invention adopts specific doping elements and forms a secondary phase, which can effectively reduce the sintering temperature of the ceramic material and is beneficial to energy saving. The enhanced zirconia ceramic provided by the present invention introduces a magnesium-containing secondary phase of a specific composition and content. Compared with conventional zirconia ceramic products, it has a significantly reduced density and high impact resistance. While having good mechanical properties, it is further lightweight and can well meet the performance requirements of electronic product shells, such as mobile phone back panels, watch cases or ceramic antennas. DETAILED DESCRIPTION

[0023] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0024] The first aspect of the present invention provides a reinforced zirconia ceramic, wherein the ceramic comprises, in terms of elements, Zr, Y, Mg, and Al; the physical phase of the ceramic comprises: tetragonal zirconia and a secondary phase, wherein the secondary phase is MgAl 12 O 19 and / or MgAl 2 O 4 ; The tetragonal zirconia is a solid solution formed by yttrium oxide and zirconium oxide.

[0025] According to the present invention, in the reinforced zirconia ceramic, the molar ratio α of Mg to Al satisfies: 1 / 12≤α≤1 / 2.

[0026] According to the present invention, preferably, based on the total weight of the ceramic, the ceramic comprises, in terms of elements, 20.65-72.1 wt% Zr, 0.61-5.45 wt% Y, 0.0037-11.83 wt% Mg, 0.038-34.78 wt% Al. In the present invention, the elemental composition of the ceramic material can be determined by XRF. Further preferably, the ceramic comprises: 27.53-69.94 wt% Zr, 0.81-5.28 wt% Y, 0.11-10.14 wt% Mg, 1.14-29.81 wt% Al.

[0027] According to the present invention, the reinforced zirconia ceramic, in addition to the above elements, also contains oxygen and negligible impurity elements that have no effect on the performance of the reinforced zirconia ceramic.

[0028] In the present invention, the molar ratio of Mg to Al in the reinforced zirconia ceramic can be controlled to obtain a secondary phase with a specific composition and structure. Specifically, when the molar ratio α of Mg to Al satisfies: α=1 / 12, the secondary phase is MgAl 12 O 19 When the molar ratio of Mg to Al satisfies: 1 / 12<α<1 / 2, the secondary phase is MgAl 12 O 19 and MgAl 2 O 4 When the molar ratio of Mg to Al satisfies: α = 1 / 2, the secondary phase is MgAl 2 O 4 For the secondary phase described in the present invention, MgAl 12 O 19 All of them exist in the reinforced zirconia ceramics in the form of whiskers, MgAl 2 O 4 The inventors of the present invention have found that by doping a specific content of whisker-shaped MgAl into a zirconia matrix,12 O 19 , or doped spinel structured MgAl 2 O 4 , or doped MgAl in whisker form 12 O 19 MgAl with spinel structure 2 O 4 The mixture of the two can improve the mechanical properties of the prepared zirconia ceramics, especially the impact resistance, and has low density, low dielectric constant, low light transmittance and good processing performance. 12 O 19 The aspect ratio of the whiskers is ≥4.

[0029] According to the present invention, the reinforced zirconia ceramic has a specific phase content. Preferably, based on the total weight of the ceramic, the phase of the ceramic comprises: more than 30wt% of tetragonal zirconia and less than 70wt% of secondary phase. The tetragonal zirconia more specifically refers to tetragonal crystals that are stable at room temperature and are formed by yttrium oxide as a stabilizer and zirconium oxide. In the present invention, the phase content of the ceramic material can be determined by XRD.

[0030] In the present invention, the magnesium-containing phase MgAl is formed 2 O 4 It helps to reduce the sintering temperature of the ceramic material, compared with the secondary phase being all MgAl 12 O 19 In the case of 2 O 4 Or MgAl 12 O 19 and MgAl 2 O 4 The mixture of the two phases can achieve a lower product sintering temperature, thereby reducing energy consumption.

[0031] In the present invention, the reinforced zirconia ceramic contains the above-mentioned specific element composition and has a subphase with a specific composition and structure, which can play a synergistic role to obtain comprehensive performances of high impact resistance, low density, low dielectric constant, low light transmittance, and good processability. When the element composition, phase type and content are not within the above-mentioned limited range, the reinforced zirconia ceramic that meets the performance parameters of the present invention cannot be obtained.

[0032] According to the present invention, preferably, the dielectric constant of the ceramic is 15-35.5 and the density is not more than 6g / cm 3 , hardness is not greater than 1400Hv, transmittance is less than 20%, drop hammer height is greater than 25cm, and thinning speed is greater than 28 wires / h.

[0033] In the present invention, a drop hammer impact test is performed and the impact resistance of the ceramic is evaluated by the drop hammer height. Specifically, a sample is placed on a test platform, and a drop hammer weighing 60g is used to hit the center of the sample. The sample is dropped from a height of 5cm. If the sample does not crack, the sample height is increased by 5cm and the sample is continued to be hit. The above operation is repeated until cracks visible to the naked eye appear on the sample, and the final height value (drop hammer height) is recorded; the dielectric constant is measured at 2GHz using a network analyzer to test the material; the hardness is measured using a hardness tester and an indentation method (diamond indenter, force 10kg, test pressure time 15s); the transmittance is measured using a Shimadzu spectrophotometer; the thinning speed is measured using a dimensional speed under a copper grinding disc, such as a fixed time of 1h, and the thickness difference before and after copper grinding is tested. The faster the thinning speed, the better the processability of the material.

[0034] In the present invention, the reinforced zirconia ceramic can obtain a test result of a drop hammer height greater than 25 cm in a drop hammer impact test, showing high impact resistance. In a preferred case, the drop hammer height of the ceramic can reach 39 cm.

[0035] In the present invention, the dielectric constant of the reinforced zirconia ceramic is 15-35.5, and the density is not more than 6g / cm 3 , with lower dielectric constant and density.

[0036] In the present invention, the light transmittance of the reinforced zirconia ceramic is lower than 20%, which can meet the requirements of electronic products for low light transmittance of ceramic shells.

[0037] In the present invention, the hardness of the reinforced zirconia ceramic is not greater than 1400 Hv, the thinning rate is greater than 28 wires / h, and the ceramic has good processability while meeting the hardness requirement.

[0038] According to the present invention, more specifically, the ceramic comprises: more than 90wt% of tetragonal zirconium oxide, less than 10wt% of secondary phase, and the dielectric constant of the ceramic is 30-35.5, which can meet the performance requirements of being used as a ceramic backplane of electronic products;

[0039] Alternatively, the ceramic comprises: 70-90wt% of tetragonal zirconium oxide, 10-30wt% of a secondary phase, and the dielectric constant of the ceramic is 20-30, which can meet the performance requirements for use as a case for electronic products;

[0040] Alternatively, the ceramic comprises: 30wt% or more and less than 70wt% of tetragonal zirconia, more than 30wt% and less than 70wt% of a secondary phase, and the dielectric constant of the ceramic is 15-20, which can meet the performance requirements for use as a ceramic antenna.

[0041] In the present invention, the reinforced zirconia ceramic can have different uses according to the different elemental compositions and phase contents, which are described in the following three cases:

[0042] Based on the total weight of the ceramic, the ceramic comprises, in terms of elements, 20.65-50.47wt% of Zr, 0.61-3.82wt% of Y, 1.11-11.83wt% of Mg, and 11.41-34.78wt% of Al, and the phase comprises: 30wt% or more and less than 70wt% of tetragonal zirconium oxide, and more than 30wt% and less than 70wt% of a secondary phase, and the dielectric constant of the ceramic is 15-20, which can meet the performance requirements for use as a ceramic antenna;

[0043] Further preferably, based on the total weight of the ceramic, the ceramic comprises, in terms of elements: 27.53-43.26wt% Zr, 0.81-3.27wt% Y, 1.47-10.14wt% Mg, 15.21-29.81wt% Al, and the phase comprises: 40-60wt% tetragonal zirconium oxide, 40-60wt% secondary phase, and the dielectric constant of the ceramic is 15-18.5, thereby better meeting the performance requirements as a ceramic antenna;

[0044] Alternatively, the ceramic contains, in terms of elements, 50.47-64.89wt% Zr, 1.43-4.91wt% Y, 0.36-5.07wt% Mg, 3.81-14.9wt% Al, and the phase contains 70-90wt% tetragonal zirconium oxide, 10-30wt% secondary phase, and the dielectric constant of the ceramic is 20-30, which can meet the performance requirements for use as a watch case for electronic products;

[0045] Further preferably, the ceramic contains, in terms of elements, 54.07-61.29wt% Zr, 1.53-4.64wt% Y, 0.54-4.23wt% Mg, 5.72-12.41wt% Al, and the phase contains 75-85wt% tetragonal zirconium oxide, 15-25wt% secondary phase, and the dielectric constant of the ceramic is 22-28, thereby better meeting the performance requirements for use as a watch case for electronic products;

[0046] Alternatively, the ceramic contains, in terms of elements, 64.89-72.1wt% Zr, 1.85-5.45wt% Y, 0.0037-1.69wt% Mg, 0.038-4.96wt% Al, and the physical phase contains: more than 90wt% tetragonal zirconia and less than 10wt% secondary phase, and the dielectric constant of the ceramic is 30-35.5, which can meet the performance requirements for use as a ceramic backplane for electronic products.

[0047] Further preferably, the ceramic contains, in terms of elements: 67.05-69.94wt% Zr, 1.92-5.28wt% Y, 0.11-1.18wt% Mg, 1.14-3.48wt% Al, and the physical phase contains: 93-97wt% tetragonal zirconia, 3-7wt% secondary phase, and the dielectric constant of the ceramic is 31-35, thereby better meeting the performance requirements for use as a ceramic backplane for electronic products.

[0048] The reinforced zirconia ceramic provided by the present invention has high impact resistance, suitable hardness and good toughness, and the mechanical properties are significantly improved, and the balance of mechanical properties, dielectric properties, density, light transmittance, processability and other indicators is achieved.

[0049] A second aspect of the present invention provides a method for preparing a reinforced zirconia ceramic, comprising:

[0050] (1) wet-grinding a powder containing magnesium oxide, aluminum oxide and yttria-stabilized zirconium oxide with water, a dispersant and a binder to obtain a slurry;

[0051] (2) drying the slurry to obtain a composite powder;

[0052] (3) forming and sintering the composite powder in sequence to obtain ceramics;

[0053] The molar ratio of magnesium oxide to aluminum oxide in the powder is γ, and 1 / 6≤γ≤1.

[0054] According to the present invention, in step (1), in the raw materials used to prepare the slurry, preferably, the weight ratio of the dispersant: binder: powder is (0.5-1): (3-5): 100, so as to ensure the grinding effect and facilitate the molding of the powder in the subsequent steps.

[0055] In the present invention, the selection of a suitable dispersant can promote the uniform dispersion of the raw material powder in water to form a slurry, and play a grinding aid role, thereby obtaining the desired grinding effect. Preferably, the dispersant is selected from at least one of hydroxypropyl methylcellulose, sodium carboxymethyl cellulose and triethanolamine. In the present invention, the dispersant can be commercially available.

[0056] In the present invention, the binder can make the powder have better formability. Preferably, the binder is selected from polyvinyl alcohol and / or polyethylene glycol, more preferably polyvinyl alcohol and polyethylene glycol, more preferably polyvinyl alcohol and polyethylene glycol are used together in a molar ratio of 1: (1-2). Specifically, the average molecular weight of polyvinyl alcohol is 60000-200000, and the average molecular weight of polyethylene glycol is 2000-6000. Furthermore, polyethylene glycol is preferably polyethylene glycol 4000. In the present invention, the binder can be commercially obtained.

[0057] According to the present invention, in step (1), preferably, based on the total weight of the powder, the powder contains: less than or equal to 19.72wt% of magnesium oxide, less than or equal to 65.71wt% of aluminum oxide, and 30-99.9wt% of yttria-stabilized zirconia; further preferably, the powder contains: 0.18-16.91wt% of magnesium oxide, 2.15-56.32wt% of aluminum oxide, and 40-97wt% of yttria-stabilized zirconia.

[0058] In the present invention, the feed amount of each raw material powder meets the elemental composition of the finally obtained enhanced zirconia ceramic, and by controlling the molar ratio γ of magnesium oxide to aluminum oxide in the powder to be 1 / 6≤γ≤1, a specific secondary phase can be obtained during the high-temperature sintering process, and the doping of the secondary phase can significantly enhance the zirconia matrix. Specifically, when γ=1 / 6, the secondary phase in the obtained enhanced zirconia ceramic is MgAl in the form of whiskers. 12 O 19 When 1 / 6<γ<1, the secondary phase in the obtained enhanced zirconia ceramic is MgAl in the form of whiskers. 12 O 19 and spinel structured MgAl 2 O 4 When γ=1, the secondary phase of the obtained enhanced zirconia ceramic is MgAl with spinel structure. 2 O 4 .

[0059] According to the present invention, in step (1), the raw materials magnesium oxide, aluminum oxide and yttria-stabilized zirconia are in the form of high-purity powders. Preferably, the median particle size of magnesium oxide is 0.3-1 μm; the median particle size of aluminum oxide is 0.15-0.6 μm; the median particle size of yttria-stabilized zirconia is 0.3-0.6 μm, and the specific surface area is 7-13 m 2 / g, which is conducive to obtaining better grinding effect.

[0060] In the present invention, the yttria-stabilized zirconia contains yttria. Preferably, based on the total amount of the yttria-stabilized zirconia, the yttria-stabilized zirconia contains 1.5-4 mol% of yttria.

[0061] In addition, each raw material powder used in the present invention may contain negligible impurities that have no effect on the performance of the reinforced zirconia ceramic.

[0062] According to the present invention, in step (1), wet grinding is used to reduce the particle size of each raw material powder to meet the preparation requirements of the enhanced zirconia ceramic. In order to obtain higher grinding efficiency and better grinding effect, it is preferred to adopt a process of first ball milling and then sand milling, and the preliminary grinding is achieved by ball milling, so that the particle size of the powder is greatly reduced and a more uniformly mixed slurry is obtained; further ultrafine grinding is achieved by sand milling to obtain a slurry that meets the process requirements. Specifically, the wet grinding process can be: the powder containing magnesium oxide, aluminum oxide and yttria-stabilized zirconium oxide is ball milled for 8-10 hours in a ball mill, and then a dispersant and water are added to a sand mill for sand milling for 8-10 hours, and finally a binder is added and stirred for 2-4 hours to obtain the slurry.

[0063] According to the present invention, in step (1), preferably, the median particle size of the solid phase component in the slurry is 0.3-0.8 μm.

[0064] In the present invention, the particle size of the grinding balls used in the wet grinding, the grading of grinding balls of different particle sizes, the weight ratio of the grinding balls to the raw material powder, the amount of water used and the working parameters of the mill can all be set and adjusted by methods well known in the art, as long as the slurry obtained by wet grinding can meet the above-mentioned median particle size range of the solid phase component.

[0065] In the present invention, the ball mill and sand mill used in the wet grinding preferably use linings and grinding balls made of zirconium oxide to better meet the requirements of the wet grinding process and to avoid impurities from being mixed into the material during the grinding process to cause pollution.

[0066] According to the present invention, in step (2), various drying methods in the art can be used, preferably spray drying. Further preferably, the process parameters of spray drying include: air inlet temperature of 200-300°C, air outlet temperature of 90-130°C, and centrifugal speed of 10-20 revolutions per second. The composite powder obtained after drying has better fluidity, which is beneficial to subsequent molding.

[0067] According to the present invention, in step (3), the process of forming is limited to a wide range, including but not limited to dry pressing, isostatic pressing, injection molding, hot die casting, etc. Preferably, dry pressing is used to obtain a high-quality green body. For example, a press with a tonnage of 180-200 tons can be used to form the composite powder under an oil pressure of 8MPa to obtain a green body. The shape of the green body can be, for example, the shape of a mobile phone back panel, the shape of a smart watch case, the shape of an antenna, etc.

[0068] According to the present invention, in step (3), conventional equipment for ceramic sintering can be used to sinter the formed green body, which can be carried out in an air atmosphere. The sintering conditions include: a temperature of 1400-1700°C, preferably 1450-1650°C; and a time of 1-5h, preferably 1-2h.

[0069] According to the present invention, the preparation method further comprises: after step (3), flat grinding and polishing the sintered ceramic, and then cutting with a laser to obtain a final product.

[0070] The third aspect of the present invention provides a reinforced zirconia ceramic prepared by the preparation method described in the second aspect. The reinforced zirconia ceramic has high impact resistance, low density, low dielectric constant, low light transmittance and good processing performance.

[0071] The ceramic contains Zr, Y, Mg and Al in terms of elements. The ceramic phases contain tetragonal zirconium oxide and a secondary phase, wherein the secondary phase is MgAl 12 O 19 and / or MgAl 2 O 4 ; The tetragonal zirconia is a solid solution formed by yttria and zirconia; wherein, in the reinforced zirconia ceramic, the molar ratio α of Mg and Al satisfies: 1 / 12≤α≤1 / 2.

[0072] Preferably, based on the total weight of the ceramic, the ceramic comprises, in terms of elements: 20.65-72.1 wt% Zr, 0.61-5.45 wt% Y, 0.0037-11.83 wt% Mg, 0.038-34.78 wt% Al;

[0073] Further preferably, the ceramic comprises: 27.53-69.94 wt % Zr, 0.81-5.28 wt % Y, 0.11-10.14 wt % Mg, 1.14-29.81 wt % Al.

[0074] In the reinforced zirconia ceramic, when the molar ratio α of Mg to Al satisfies: α=1 / 12, the secondary phase is MgAl 12 O19 When the molar ratio of Mg to Al satisfies: 1 / 12<α<1 / 2, the secondary phase is MgAl 12 O 19 and MgAl 2 O 4 When the molar ratio of Mg to Al satisfies: α = 1 / 2, the secondary phase is MgAl 2 O 4 .

[0075] In the reinforced zirconia ceramic, MgAl 12 O 19 In the form of whiskers; the MgAl 12 O 19 The aspect ratio of whiskers is ≥4; MgAl 2 O 4 It has a spinel structure.

[0076] In the reinforced zirconia ceramic, based on the total weight of the ceramic, the physical phase of the ceramic comprises: more than 30wt% of tetragonal zirconia and less than 70wt% of secondary phase; specifically, the ceramic comprises: more than 90wt% of tetragonal zirconia and less than 10wt% of secondary phase, and the dielectric constant of the ceramic is 30-35.5; or the ceramic comprises: 70-90wt% of tetragonal zirconia and 10-30wt% of secondary phase, and the dielectric constant of the ceramic is 20-30; or the ceramic comprises: more than 30wt% and less than 70wt% of tetragonal zirconia, more than 30wt% and less than 70wt% of secondary phase, and the dielectric constant of the ceramic is 15-20.

[0077] The dielectric constant of the reinforced zirconia ceramic is 15-35.5, and the density is no more than 6g / cm 3 , hardness is not greater than 1400Hv, transmittance is less than 20%, drop hammer height is greater than 25cm, and thinning speed is greater than 28 wires / h.

[0078] A fourth aspect of the present invention provides an electronic product housing, wherein the electronic product housing comprises the reinforced zirconia ceramic described in the first aspect or the third aspect.

[0079] The present invention will be described in detail below by way of examples. In the following examples and comparative examples,

[0080] Phase types and contents in ceramic products: measured by XRD test using Smartlab (3kW) X-ray diffractometer;

[0081] Element content in ceramic products: measured by XRF test using energy dispersive X-ray fluorescence spectrometer EDX-7000;

[0082] Hardness Hv: hardness tester and indentation method (diamond indenter, force 10kg, test time 15s);

[0083] Fracture toughness Kic: hardness tester indentation method (diamond indenter, force 10kg, test time 15s);

[0084] Density: The average number of pits (greater than 20um) within a range of 10*10mm on the large surface of the product;

[0085] Light transmittance: tested using Shimadzu spectrophotometer;

[0086] Dielectric constant: Use a network analyzer to test the dielectric constant of the material at 2GHz;

[0087] Processability: the dimensional speed of the copper grinding disc, for example, the fixed time is 1 hour, the thickness difference before and after copper grinding is tested, and the thinning speed (wire / h) is recorded;

[0088] Drop hammer impact: Use a drop hammer impact tester (manufacturer CKSI, model E602SS), place the sample on the test platform, use a 60g drop hammer to hit the center of the sample, start dropping the hammer from a height of 5cm, if the sample does not crack, increase the height by 5cm and continue to hit the sample, repeat the above operation until visible cracks appear on the sample, and record the final height value.

[0089] Example 1

[0090] Raw material powder: 200g composite powder, containing 8.57wt% magnesium oxide (MgO), 41.43wt% aluminum oxide (Al 2 O 3 ), 50wt% of zirconia stabilized with 3mol% yttria.

[0091] (1) The raw material powder and water were added to a ball mill and ball-milled for 8 h. The resulting slurry was transferred to a sand mill, and 0.7 wt% of hydroxypropyl methylcellulose was added to the raw material powder. Water was added and sand-milled for 10 h. Finally, 3 wt% of the binder (PEG4000 and PVA in a molar ratio of 1:1) was added to the raw material powder and stirred for 0.5 h to obtain a slurry (the median particle size of the solid phase component was 0.5 μm);

[0092] (2) sending the slurry into a spray tower for spray drying (drying parameters: inlet air temperature of 250°C, outlet air temperature of 110°C, centrifugal speed of 15 revolutions per second) to obtain a composite powder with strong fluidity;

[0093] (3) dry pressing the composite powder (using a 200-ton press at an oil pressure of 8 MPa) to obtain a green body; sintering the green body at 1600° C. for 2 h in an air atmosphere to obtain a ceramic;

[0094] (4) The sintered ceramics were ground and polished and laser cut to a size of 150*75*0.6 mm to obtain the final product (denoted as S1).

[0095] S1 was tested by XRF and XRD, and the results were:

[0096] The constituent elements of S1 include 35.1 wt% Zr, 2.2 wt% Y, 5.2 wt% Mg, and 22.1 wt% Al.

[0097] The phases of S1 include: tetragonal zirconia 49.5wt%, MgAl 12 O 19 25.1wt%,MgAl 2 O 4 The content of yttrium oxide is 25.2wt%, and the content of monoclinic zirconium oxide is 0.2wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0098] Example 2

[0099] Raw material powder: 200g composite powder, containing 11.15wt% magnesium oxide (MgO), 53.85wt% aluminum oxide (Al 2 O 3 ), 35wt% of zirconia stabilized with 3mol% yttria.

[0100] (1) The raw material powder and water were added to a ball mill and ball-milled for 8 h. The resulting slurry was transferred to a sand mill, and 0.7 wt% of hydroxypropyl methylcellulose was added to the raw material powder. Water was added and sand-milled for 10 h. Finally, 3 wt% of the binder (PEG4000 and PVA in a molar ratio of 1:1) was added to the raw material powder and stirred for 0.5 h to obtain a slurry (the median particle size of the solid phase component was 0.5 μm);

[0101] (2) sending the slurry into a spray tower for spray drying (drying parameters: inlet air temperature of 250°C, outlet air temperature of 110°C, centrifugal speed of 15 revolutions per second) to obtain a composite powder with strong fluidity;

[0102] (3) dry pressing the composite powder (using a 200-ton press at an oil pressure of 8 MPa) to obtain a green body; sintering the green body at 1600° C. for 2 h in an air atmosphere to obtain a ceramic;

[0103] (4) The sintered ceramics were ground and polished and laser cut to a size of 150*75*0.6 mm to obtain the final product (denoted as S2).

[0104] S2 was tested by XRF and XRD, and the results were:

[0105] The constituent elements of S2 include 24.6 wt% Zr, 1.7 wt% Y, 6.8 wt% Mg and 28.9 wt% Al.

[0106] The phases of S2 include: 34.4wt% tetragonal zirconia, MgAl 12 O 19 32.7wt%,MgAl 2 O 4 The content of yttrium oxide is 32.8wt%, and the content of monoclinic zirconium oxide is 0.1wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0107] Example 3

[0108] Raw material powder: 200g composite powder, containing 6wt% magnesium oxide (MgO), 29wt% aluminum oxide (Al 2 O 3 ), 65wt% of zirconia stabilized with 3mol% yttria.

[0109] (1) The raw material powder and water were added to a ball mill and ball-milled for 8 h. The resulting slurry was transferred to a sand mill, and 0.7 wt% of hydroxypropyl methylcellulose was added to the raw material powder. Water was added and sand-milled for 10 h. Finally, 3 wt% of the binder (PEG4000 and PVA in a molar ratio of 1:1) was added to the raw material powder and stirred for 0.5 h to obtain a slurry (the median particle size of the solid phase component was 0.5 μm);

[0110] (2) sending the slurry into a spray tower for spray drying (drying parameters: inlet air temperature of 250°C, outlet air temperature of 110°C, centrifugal speed of 15 revolutions per second) to obtain a composite powder with strong fluidity;

[0111] (3) dry pressing the composite powder (using a 200-ton press at an oil pressure of 8 MPa) to obtain a green body; sintering the green body at 1600° C. for 2 h in an air atmosphere to obtain a ceramic;

[0112] (4) The sintered ceramics were ground and polished and laser cut to a size of 150*75*0.6 mm to obtain the final product (denoted as S3).

[0113] S3 was tested by XRF and XRD, and the results were:

[0114] The constituent elements of S3 include 45.7 wt% Zr, 3.3 wt% Y, 3.7 wt% Mg and 15.7 wt% Al.

[0115] The phases of S3 include: tetragonal zirconia 64.4wt%, MgAl12 O 19 17.6wt%,MgAl 2 O 4 The content of yttrium oxide is 17.7wt%, and the content of monoclinic zirconium oxide is 0.3wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0116] Example 4

[0117] Raw material powder: 200g composite powder, containing 3.07wt% magnesium oxide (MgO), 46.93wt% aluminum oxide (Al 2 O 3 ), 50wt% of zirconia stabilized with 3mol% yttria.

[0118] (1) The raw material powder and water were added to a ball mill and ball-milled for 8 h. The resulting slurry was transferred to a sand mill, and 0.7 wt% of hydroxypropyl methylcellulose was added to the raw material powder. Water was added and sand-milled for 10 h. Finally, 3 wt% of the binder (PEG4000 and PVA in a molar ratio of 1:1) was added to the raw material powder and stirred for 0.5 h to obtain a slurry (the median particle size of the solid phase component was 0.5 μm);

[0119] (2) sending the slurry into a spray tower for spray drying (drying parameters: inlet air temperature of 250°C, outlet air temperature of 110°C, centrifugal speed of 15 revolutions per second) to obtain a composite powder with strong fluidity;

[0120] (3) dry pressing the composite powder (using a 200-ton press at an oil pressure of 8 MPa) to obtain a green body; sintering the green body at 1630° C. for 2 h in an air atmosphere to obtain a ceramic;

[0121] (4) The sintered ceramic is ground and polished and laser cut to a size of 150*75*0.6 mm to obtain the final product (denoted as S4).

[0122] S4 was tested by XRF and XRD, and the results were:

[0123] The constituent elements of S4 include 35.2 wt% Zr, 2.3 wt% Y, 1.9 wt% Mg and 24.9 wt% Al.

[0124] The phases of S4 include: tetragonal zirconia 49.3wt%, MgAl 12 O 19 The content of yttrium oxide is 50.3wt%, and the content of monoclinic zirconium oxide is 0.4wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0125] Example 5

[0126] Raw material powder: 200g composite powder, containing 14.08wt% magnesium oxide (MgO), 35.92wt% aluminum oxide (Al 2 O 3 ), 50wt% of zirconia stabilized with 3mol% yttria.

[0127] (1) The raw material powder and water were added to a ball mill and ball-milled for 8 h. The resulting slurry was transferred to a sand mill, and 0.7 wt% of hydroxypropyl methylcellulose was added to the raw material powder. Water was added and sand-milled for 10 h. Finally, 3 wt% of the binder (PEG4000 and PVA in a molar ratio of 1:1) was added to the raw material powder and stirred for 0.5 h to obtain a slurry (the median particle size of the solid phase component was 0.5 μm);

[0128] (2) sending the slurry into a spray tower for spray drying (drying parameters: inlet air temperature of 250°C, outlet air temperature of 110°C, centrifugal speed of 15 revolutions per second) to obtain a composite powder with strong fluidity;

[0129] (3) dry pressing the composite powder (using a 200-ton press at an oil pressure of 8 MPa) to obtain a green body; sintering the green body at 1580° C. for 2 h in an air atmosphere to obtain a ceramic;

[0130] (4) The sintered ceramic is ground and polished and laser cut to a size of 150*75*0.6 mm to obtain a final product (denoted as S5).

[0131] The S5 was tested by XRF and XRD, and the results were:

[0132] The constituent elements of S5 include 35.3 wt % Zr, 2.2 wt % Y, 8.5 wt % Mg and 19.1 wt % Al.

[0133] The phases of S5 include: tetragonal zirconia 49.5wt%, MgAl 2 O 4 The content of yttrium oxide is 50.1wt%, and the content of monoclinic zirconium oxide is 0.4wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0134] Example 6

[0135] Raw material powder: 200g composite powder, containing 3.43wt% magnesium oxide (MgO), 16.57wt% aluminum oxide (Al 2 O 3 ), 80wt% of zirconia stabilized with 3mol% yttria.

[0136] (1) The raw material powder and water were added to a ball mill and ball-milled for 8 h. The resulting slurry was transferred to a sand mill, and 0.7 wt% of hydroxypropyl methylcellulose was added to the raw material powder. Water was added and sand-milled for 10 h. Finally, 3 wt% of the binder (PEG4000 and PVA in a molar ratio of 1:1) was added to the raw material powder and stirred for 0.5 h to obtain a slurry (the median particle size of the solid phase component was 0.5 μm);

[0137] (2) sending the slurry into a spray tower for spray drying (drying parameters: inlet air temperature of 250°C, outlet air temperature of 110°C, centrifugal speed of 15 revolutions per second) to obtain a composite powder with strong fluidity;

[0138] (3) dry pressing the composite powder (using a 200-ton press at an oil pressure of 8 MPa) to obtain a green body; sintering the green body at 1550° C. for 2 h in an air atmosphere to obtain a ceramic;

[0139] (4) The sintered ceramic is ground and polished and laser cut to a size of 150*75*0.6 mm to obtain a final product (denoted as S6).

[0140] S6 was tested by XRF and XRD, and the results were:

[0141] The constituent elements of S6 include 56.4 wt% Zr, 3.5 wt% Y, 2.3 wt% Mg and 9.1 wt% Al.

[0142] The phases of S6 include: tetragonal zirconia 79.6wt%, MgAl 12 O 19 10.1wt%,MgAl 2 O 4 The content of yttrium oxide is 10.2wt%, and the content of monoclinic zirconium oxide is 0.1wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0143] Example 7

[0144] Raw material powder: 200g composite powder, containing 4.80wt% magnesium oxide (MgO), 23.20wt% aluminum oxide (Al 2 O 3 ), 72wt% of zirconia stabilized with 3mol% yttria.

[0145] (1) The raw material powder and water were added to a ball mill and ball-milled for 8 h. The resulting slurry was transferred to a sand mill, and 0.7 wt% of hydroxypropyl methylcellulose was added to the raw material powder. Water was added and sand-milled for 10 h. Finally, 3 wt% of the binder (PEG4000 and PVA in a molar ratio of 1:1) was added to the raw material powder and stirred for 0.5 h to obtain a slurry (the median particle size of the solid phase component was 0.5 μm);

[0146] (2) sending the slurry into a spray tower for spray drying (drying parameters: inlet air temperature of 250°C, outlet air temperature of 110°C, centrifugal speed of 15 revolutions per second) to obtain a composite powder with strong fluidity;

[0147] (3) dry pressing the composite powder (using a 200-ton press at an oil pressure of 8 MPa) to obtain a green body; sintering the green body at 1550° C. for 2 h in an air atmosphere to obtain a ceramic;

[0148] (4) The sintered ceramic is ground and polished and laser cut to a size of 150*75*0.6 mm to obtain a final product (denoted as S7).

[0149] The S7 was tested by XRF and XRD, and the results were:

[0150] The constituent elements of S7 include 50.8 wt % Zr, 3.2 wt % Y, 3.3 wt % Mg and 12.9 wt % Al.

[0151] The phases of S7 include: tetragonal zirconia 71.5wt%, MgAl 12 O 19 14.1wt%,MgAl 2 O 4 The content of yttrium oxide is 14.2 wt%, and the content of monoclinic zirconium oxide is 0.2 wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0152] Example 8

[0153] Raw material powder: 200g composite powder, containing 2.05wt% magnesium oxide (MgO), 9.95wt% aluminum oxide (Al 2 O 3 ), 88wt% of zirconia stabilized with 3mol% yttria.

[0154] (1) The raw material powder and water were added to a ball mill and ball-milled for 8 h. The resulting slurry was transferred to a sand mill, and 0.7 wt% of hydroxypropyl methylcellulose was added to the raw material powder. Water was added and sand-milled for 10 h. Finally, 3 wt% of the binder (PEG4000 and PVA in a molar ratio of 1:1) was added to the raw material powder and stirred for 0.5 h to obtain a slurry (the median particle size of the solid phase component was 0.5 μm);

[0155] (2) sending the slurry into a spray tower for spray drying (drying parameters: inlet air temperature of 250°C, outlet air temperature of 110°C, centrifugal speed of 15 revolutions per second) to obtain a composite powder with strong fluidity;

[0156] (3) dry pressing the composite powder (using a 200-ton press at an oil pressure of 8 MPa) to obtain a green body; sintering the green body at 1550° C. for 2 h in an air atmosphere to obtain a ceramic;

[0157] (4) The sintered ceramic is ground and polished and laser cut to a size of 150*75*0.6 mm to obtain a final product (denoted as S8).

[0158] The S8 was tested by XRF and XRD, and the results were:

[0159] The constituent elements of S8 include 62.1 wt% Zr, 3.3 wt% Y, 1.5 wt% Mg and 5.6 wt% Al.

[0160] The phases of S8 include: tetragonal zirconia 87.4wt%, MgAl 12 O 19 6.1wt%,MgAl 2 O 4 The content of yttrium oxide is 6.3wt%, and the content of monoclinic zirconium oxide is 0.2wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0161] Example 9

[0162] Raw material powder: 200g composite powder, containing 1.23wt% magnesium oxide (MgO), 18.77wt% aluminum oxide (Al 2 O 3 ), 80wt% of zirconia stabilized with 3mol% yttria.

[0163] (1) The raw material powder and water are added to a ball mill and ball milled for 8 hours. The resulting slurry is transferred to a sand mill, and 0.7 wt% of hydroxypropyl methylcellulose is added to the raw material powder, water is added, and sand milling is performed for 10 hours. Finally, a binder (PEG4000 and PVA with a molar ratio of 1:1) accounting for 3 wt% of the raw material powder is added and stirred for 0.5 hours to obtain a slurry solid phase component with a particle size median of 0.5 μm);

[0164] (2) sending the slurry into a spray tower for spray drying (drying parameters: inlet air temperature of 250°C, outlet air temperature of 110°C, centrifugal speed of 15 revolutions per second) to obtain a composite powder with strong fluidity;

[0165] (3) dry pressing the composite powder (using a 200-ton press at an oil pressure of 8 MPa) to obtain a green body; sintering the green body at 1570° C. for 2 h in an air atmosphere to obtain a ceramic;

[0166] (4) The sintered ceramic is ground and polished and laser cut to a size of 150*75*0.6 mm to obtain a final product (denoted as S9).

[0167] The S9 was tested by XRF and XRD, and the results were:

[0168] The constituent elements of S9 include 56.5 wt % of Zr, 4.1 wt % of Y, 0.8 wt % of Mg, and 10.1 wt % of Al.

[0169] The phases of S9 include: tetragonal zirconia 79.4wt%, MgAl 12 O 19 The content of yttrium oxide is 20.4wt%, and the content of monoclinic zirconium oxide is 0.2wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0170] Example 10

[0171] Raw material powder: 200g composite powder, containing 5.63wt% magnesium oxide (MgO), 14.36wt% aluminum oxide (Al 2 O 3 ), 80wt% of zirconia stabilized with 3mol% yttria.

[0172] (1) The raw material powder and water are added to a ball mill and ball milled for 8 hours. The resulting slurry is transferred to a sand mill, and 0.7 wt% of hydroxypropyl methylcellulose is added to the raw material powder, water is added, and sand milling is performed for 10 hours. Finally, a binder (PEG4000 and PVA with a molar ratio of 1:1) accounting for 3 wt% of the raw material powder is added and stirred for 0.5 hours to obtain a slurry solid phase component with a particle size median of 0.5 μm);

[0173] (2) sending the slurry into a spray tower for spray drying (drying parameters: inlet air temperature of 250°C, outlet air temperature of 110°C, centrifugal speed of 15 revolutions per second) to obtain a composite powder with strong fluidity;

[0174] (3) dry pressing the composite powder (using a 200-ton press at an oil pressure of 8 MPa) to obtain a green body; sintering the green body at 1530° C. for 2 h in an air atmosphere to obtain a ceramic;

[0175] (4) The sintered ceramic is ground and polished and laser cut to a size of 150*75*0.6 mm to obtain a final product (denoted as S10).

[0176] The S10 was tested by XRF and XRD, and the results were:

[0177] The constituent elements of S10 include 56.6 wt % Zr, 3.4 wt % Y, 3.4 wt % Mg and 7.7 wt % Al.

[0178] The phases of S10 include: tetragonal zirconia 79.4wt%, MgAl 2 O 4 The content of yttrium oxide is 20.5wt%, and the content of monoclinic zirconium oxide is 0.1wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0179] Embodiment 11

[0180] Raw material powder: 200g composite powder, containing 0.86wt% magnesium oxide (MgO), 4.14wt% aluminum oxide (Al 2 O 3 ), 95wt% of zirconia stabilized with 3mol% yttria.

[0181] (1) The raw material powder and water were added to a ball mill and ball-milled for 8 h. The resulting slurry was transferred to a sand mill, and 0.5 wt% of hydroxypropyl methylcellulose was added to the raw material powder, water was added, and sand milled for 10 h. Finally, 3 wt% of the binder (PEG4000 and PVA with a molar ratio of 1:1) was added to the raw material powder and stirred for 0.5 h to obtain a slurry (the median particle size of the solid phase component was 0.5 μm);

[0182] (2) sending the slurry into a spray tower for spray drying (drying parameters: inlet air temperature of 250°C, outlet air temperature of 110°C, centrifugal speed of 15 revolutions per second) to obtain a composite powder with strong fluidity;

[0183] (3) dry pressing the composite powder (using a 200-ton press at an oil pressure of 8 MPa) to obtain a green body; sintering the green body at 1500° C. for 2 h in an air atmosphere to obtain a ceramic;

[0184] (4) The sintered ceramic is ground and polished and laser cut to a size of 150*75*0.6 mm to obtain a final product (denoted as S11).

[0185] The S11 was tested by XRF and XRD, and the results were:

[0186] The constituent elements of S11 include 67.1 wt% of Zr, 3.9 wt% of Y, 0.7 wt% of Mg, and 2.4 wt% of Al.

[0187] The phases of S11 include: 94.6wt% tetragonal zirconia, MgAl 12 O 19 2.6wt%,MgAl 2 O 4 The content of yttrium oxide is 2.6wt%, and the content of monoclinic zirconium oxide is 0.2wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0188] Example 12

[0189] Raw material powder: 200g composite powder, containing 1.46wt% magnesium oxide (MgO), 7.04wt% aluminum oxide (Al 2 O 3 ), 91.5wt% of zirconia stabilized with 3mol% yttria.

[0190] (1) The raw material powder and water were added to a ball mill and ball-milled for 8 h. The resulting slurry was transferred to a sand mill, and 0.5 wt% of hydroxypropyl methylcellulose was added to the raw material powder, water was added, and sand milled for 10 h. Finally, 3 wt% of the binder (PEG4000 and PVA with a molar ratio of 1:1) was added to the raw material powder and stirred for 0.5 h to obtain a slurry (the median particle size of the solid phase component was 0.5 μm);

[0191] (2) sending the slurry into a spray tower for spray drying (drying parameters: inlet air temperature of 250°C, outlet air temperature of 110°C, centrifugal speed of 15 revolutions per second) to obtain a composite powder with strong fluidity;

[0192] (3) dry pressing the composite powder (using a 200-ton press at an oil pressure of 8 MPa) to obtain a green body; sintering the green body at 1500° C. for 2 h in an air atmosphere to obtain a ceramic;

[0193] (4) The sintered ceramic is ground and polished and laser cut to a size of 150*75*0.6 mm to obtain a final product (denoted as S12).

[0194] The S12 was tested by XRF and XRD, and the results were:

[0195] The constituent elements of S12 are: Zr: 64.9 wt %, Y: 3.7 wt %, Mg: 1.1 wt %, and Al: 4.1 wt %.

[0196] The phases of S12 include: 91.1wt% tetragonal zirconia, MgAl 12 O 19 4.3wt%,MgAl 2 O 4 The content of yttrium oxide is 4.4wt%, and the content of monoclinic zirconium oxide is 0.2wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0197] Embodiment 13

[0198] Raw material powder: 200g composite powder, containing 0.26wt% magnesium oxide (MgO), 1.24wt% aluminum oxide (Al 2 O 3 ), 98.5wt% of zirconia stabilized with 3mol% yttria.

[0199] (1) The raw material powder and water were added to a ball mill and ball-milled for 8 h. The resulting slurry was transferred to a sand mill, and 0.5 wt% of hydroxypropyl methylcellulose was added to the raw material powder, water was added, and sand milled for 10 h. Finally, 3 wt% of the binder (PEG4000 and PVA with a molar ratio of 1:1) was added to the raw material powder and stirred for 0.5 h to obtain a slurry (the median particle size of the solid phase component was 0.5 μm);

[0200] (2) sending the slurry into a spray tower for spray drying (drying parameters: inlet air temperature of 250°C, outlet air temperature of 110°C, centrifugal speed of 15 revolutions per second) to obtain a composite powder with strong fluidity;

[0201] (3) dry pressing the composite powder (using a 200-ton press at an oil pressure of 8 MPa) to obtain a green body; sintering the green body at 1500° C. for 2 h in an air atmosphere to obtain a ceramic;

[0202] (4) The sintered ceramic is ground and polished and laser cut to a size of 150*75*0.6 mm to obtain a final product (referred to as S13).

[0203] The results of XRF and XRD tests on S13 are as follows:

[0204] The constituent elements of S13 are: Zr: 69.8 wt %, Y: 4.1 wt %, Mg: 0.2 wt %, and Al: 0.7 wt %.

[0205] The phases of S13 include: 98.2wt% tetragonal zirconia, MgAl 12 O 19 0.8wt%MgAl 2 O 4 The content of yttrium oxide is 0.8wt%, and the content of monoclinic zirconium oxide is 0.2wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0206] Embodiment 14

[0207] Raw material powder: 200g composite powder, containing 0.31wt% magnesium oxide (MgO), 4.69wt% aluminum oxide (Al 2 O 3 ), 95wt% of zirconia stabilized with 3mol% yttria.

[0208] (1) The raw material powder and water are added to a ball mill and ball milled for 8 hours. The resulting slurry is transferred to a sand mill, and 0.7 wt% of hydroxypropyl methylcellulose is added to the raw material powder, water is added, and sand milling is performed for 10 hours. Finally, a binder (PEG4000 and PVA with a molar ratio of 1:1) accounting for 3 wt% of the raw material powder is added and stirred for 0.5 hours to obtain a slurry solid phase component with a particle size median of 0.5 μm);

[0209] (2) sending the slurry into a spray tower for spray drying (drying parameters: inlet air temperature of 250°C, outlet air temperature of 110°C, centrifugal speed of 15 revolutions per second) to obtain a composite powder with strong fluidity;

[0210] (3) dry pressing the composite powder (using a 200-ton press at an oil pressure of 8 MPa) to obtain a green body; sintering the green body at 1525° C. for 2 h in an air atmosphere to obtain a ceramic;

[0211] (4) The sintered ceramic is ground and polished and laser cut to a size of 150*75*0.6 mm to obtain a final product (referred to as S14).

[0212] S14 was tested by XRF and XRD, and the results were:

[0213] The constituent elements of S14 include 67.2 wt% Zr, 3.9 wt% Y, 0.2 wt% Mg and 2.6 wt% Al.

[0214] The phases of S14 include: 94.4wt% tetragonal zirconia, MgAl12 O 19 The content of yttrium oxide is 5.4wt%, and the content of monoclinic zirconium oxide is 0.2wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0215] Embodiment 15

[0216] Raw material powder: 200g composite powder, containing 1.41wt% magnesium oxide (MgO), 3.59wt% aluminum oxide (Al 2 O 3 ), 95wt% of zirconia stabilized with 3mol% yttria.

[0217] (1) The raw material powder and water were added to a ball mill and ball-milled for 8 h. The resulting slurry was transferred to a sand mill, and 0.7 wt% of hydroxypropyl methylcellulose was added to the raw material powder. Water was added and sand-milled for 10 h. Finally, 3 wt% of the binder (PEG4000 and PVA in a molar ratio of 1:1) was added to the raw material powder and stirred for 0.5 h to obtain a slurry (the median particle size of the solid phase component was 0.5 μm);

[0218] (2) sending the slurry into a spray tower for spray drying (drying parameters: inlet air temperature of 250°C, outlet air temperature of 110°C, centrifugal speed of 15 revolutions per second) to obtain a composite powder with strong fluidity;

[0219] (3) dry pressing the composite powder (using a 200-ton press at an oil pressure of 8 MPa) to obtain a green body; sintering the green body at 1480° C. for 2 h in an air atmosphere to obtain a ceramic;

[0220] (4) The sintered ceramic is ground and polished and laser cut to a size of 150*75*0.6 mm to obtain a final product (denoted as S15).

[0221] The S15 was tested by XRF and XRD, and the results were:

[0222] The constituent elements of S15 are: Zr: 67.3 wt %, Y: 3.8 wt %, Mg: 0.9 wt %, and Al: 1.9 wt %.

[0223] The phases of S15 include: 94.6wt% tetragonal zirconia, MgAl 2 O 4 The content of yttrium oxide is 5.1wt%, and the content of monoclinic zirconium oxide is 0.3wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0224] Comparative Example 1

[0225] Raw material powder: 200g composite powder, containing 20wt% alumina (Al2 O 3 ), 80wt% of zirconia stabilized with 3mol% yttria.

[0226] (1) The raw material powder and water were added to a ball mill and ball-milled for 8 h. The resulting slurry was transferred to a sand mill, and 0.5 wt% of hydroxypropyl methylcellulose was added to the raw material powder, water was added, and sand milled for 10 h. Finally, 3 wt% of the binder (PEG4000 and PVA with a molar ratio of 1:1) was added to the raw material powder and stirred for 0.5 h to obtain a slurry (the median particle size of the solid phase component was 0.5 μm);

[0227] (2) sending the slurry into a spray tower for spray drying (drying parameters: inlet air temperature of 250°C, outlet air temperature of 110°C, centrifugal speed of 15 revolutions per second) to obtain a composite powder with strong fluidity;

[0228] (3) dry pressing the composite powder (using a 200-ton press at an oil pressure of 8 MPa) to obtain a green body; sintering the green body at 1550° C. for 2 h in an air atmosphere to obtain a ceramic;

[0229] (4) The sintered ceramic was ground and polished and laser cut to a size of 150*75*0.6 mm to obtain the final product (denoted as D1).

[0230] XRF and XRD tests were performed on D1, and the results were:

[0231] The constituent elements of D1 include 56.5 wt % of Zr, 3.3 wt % of Y, and 10.7 wt % of Al.

[0232] The phases of D1 include: tetragonal zirconia 79.6wt%, Al 2 O 3 The content of yttrium oxide is 20.1wt%, and the content of monoclinic zirconium oxide is 0.3wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0233] Comparative Example 2

[0234] Raw material powder: 200g composite powder, containing 13.72wt% magnesium oxide (MgO), 66.28wt% aluminum oxide (Al 2 O 3 ), 20wt% of zirconia stabilized with 3mol% yttria.

[0235] (1) The raw material powder and water were added to a ball mill and ball-milled for 8 h. The resulting slurry was transferred to a sand mill, and 0.5 wt% of hydroxypropyl methylcellulose was added to the raw material powder, water was added, and sand milled for 10 h. Finally, 3 wt% of the binder (PEG4000 and PVA with a molar ratio of 1:1) was added to the raw material powder and stirred for 0.5 h to obtain a slurry (the median particle size of the solid phase component was 0.5 μm);

[0236] (2) sending the slurry into a spray tower for spray drying (drying parameters: inlet air temperature of 250°C, outlet air temperature of 110°C, centrifugal speed of 15 revolutions per second) to obtain a composite powder with strong fluidity;

[0237] (3) dry pressing the composite powder (using a 200-ton press at an oil pressure of 8 MPa) to obtain a green body; sintering the green body at 1650° C. for 2 h in an air atmosphere to obtain a ceramic;

[0238] (4) The sintered ceramic was ground and polished and laser cut to a size of 150*75*0.6 mm to obtain the final product (denoted as D2).

[0239] XRF and XRD tests were performed on D2, and the results were:

[0240] The constituent elements of D2 include 14.3 wt% Zr, 0.9 wt% Y, 8.3 wt% Mg, and 35.2 wt% Al.

[0241] The phases of D2 include: tetragonal zirconia 19.4wt%, MgAl 12 O 19 40.1wt%,MgAl 2 O 4 The content of yttrium oxide is 40.3wt%, and the content of monoclinic zirconium oxide is 0.2wt%. Among them, the tetragonal zirconium oxide is a solid solution formed by yttrium oxide and zirconium oxide.

[0242] Test Example 1

[0243] The hardness, toughness, density and light transmittance of the ceramic products S1-S15 and D1-D2 prepared in Examples 1-15 and Comparative Examples 1-2 were tested respectively. The results are shown in Table 1.

[0244] Table 1

[0245]

[0246]

[0247] It can be seen from Table 1 that by introducing the secondary phase with the specific structure and content described in the present invention into the zirconia matrix, the obtained reinforced zirconia ceramic has suitable hardness, good toughness and low light transmittance.

[0248] Compared with the product D1 prepared by the prior art, the corresponding reinforced zirconia ceramic product S6 prepared by the method of the present invention has lower hardness, better toughness and lower light transmittance.

[0249] However, D2 does not have the specific element composition and phase content of the reinforced zirconia ceramic described in the present application. Although it has a lower light transmittance, its hardness is significantly higher than that of S1-S15, and its toughness is poor.

[0250] Test Example 2

[0251] The dielectric constant, density, processability and drop weight impact resistance of the ceramic products S1-S15 and D1-D2 prepared in Examples 1-15 and Comparative Examples 1-2 were tested respectively. The results are shown in Table 2.

[0252] Table 2

[0253]

[0254]

[0255] It can be seen from Table 2 that the reinforced zirconia ceramics prepared by the present invention have high impact resistance, low density, low dielectric constant and good processability, which is reflected in the drop hammer height of S1-S15 being greater than 25 cm, and the maximum can reach 39 cm; the density is lower than 6.0 g / cm 3 ; Thinning speed is greater than 28 wires / h.

[0256] Based on the above test results, the reinforced zirconia ceramics prepared by the method of the present invention, in which the magnesium-containing secondary phase with a specific morphology and content is doped, can bring about a significant reinforcement effect, so that the product can be further lightweight while having good mechanical properties, and at the same time has a low dielectric constant, low light transmittance and good processing performance, while the products prepared by Comparative Examples 1-2 cannot have the above properties.

[0257] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A reinforced zirconia ceramic, characterized in that: The ceramic comprises, in terms of elements, Zr, Y, Mg, and Al; the ceramic phase comprises: tetragonal zirconium oxide and a secondary phase, wherein the secondary phase is MgAl 12 O 19 , or the secondary phase is MgAl 12 O 19 and MgAl2O4; the tetragonal zirconia is a solid solution of yttrium oxide and zirconium oxide; Wherein, based on the total weight of the ceramic, the physical phase of the ceramic comprises: more than 30wt% of tetragonal zirconia and less than 70wt% of a secondary phase; MgAl 12 O 19 MgAl2O4 exists in the reinforced zirconia ceramic in the form of whiskers and has a spinel structure; The ceramic comprises, based on the total weight of the ceramic, 20.65-72.1 wt % of Zr, 0.61-5.45 wt % of Y, 0.0037-11.83 wt % of Mg, and 0.038-34.78 wt % of Al in terms of elements.

2. The ceramic according to claim 1, wherein The ceramic comprises, based on the total weight of the ceramic, 27.53-69.94 wt % of Zr, 0.81-5.28 wt % of Y, 0.11-10.14 wt % of Mg, and 1.14-29.81 wt % of Al in terms of elements.

3. The ceramic according to claim 1 or 2, wherein: The MgAl 12 O 19 The aspect ratio of the whiskers is ≥4.

4. The ceramic according to claim 1 or 2, wherein: The dielectric constant of the ceramic is 15-35.

5.

5. The ceramic according to claim 1 or 2, wherein: The density of the ceramic is not more than 6g / cm 3 .

6. The ceramic according to claim 1 or 2, wherein: The hardness of the ceramic is not greater than 1400 Hv.

7. The ceramic according to claim 1 or 2, wherein: The light transmittance of the ceramic is lower than 20%.

8. The ceramic according to claim 1 or 2, wherein: The ceramic thinning speed is greater than 28 wires / h.

9. The ceramic according to claim 1 or 2, wherein: The drop height of the ceramic is greater than 25 cm.

10. The ceramic according to claim 1 or 2, wherein: The ceramic comprises: more than 90 wt % of tetragonal zirconia, less than 10 wt % of a secondary phase, and the dielectric constant of the ceramic is 30-35.5; or The ceramic comprises: 70-90wt% of tetragonal zirconia, 10-30wt% of a secondary phase, and the dielectric constant of the ceramic is 20-30; or The ceramic comprises: more than 30wt% and less than 70wt% of tetragonal zirconia, more than 30wt% and less than 70wt% of a secondary phase, and the dielectric constant of the ceramic is 15-20.

11. The method for preparing the reinforced zirconia ceramic according to claim 1, characterized in that: include: (1) wet-grinding a powder containing magnesium oxide, aluminum oxide and yttria-stabilized zirconium oxide with water, a dispersant and a binder to obtain a slurry; (2) drying the slurry to obtain a composite powder; (3) forming and sintering the composite powder in sequence to obtain ceramics; The molar ratio of magnesium oxide to aluminum oxide in the powder is γ, and 1 / 6≤γ≤1.

12. The method according to claim 11, wherein: In step (1), the weight ratio of the dispersant: binder: powder is (0.5-1): (3-5): 100; And / or, the dispersant is selected from at least one of hydroxypropyl methylcellulose, sodium carboxymethyl cellulose and triethanolamine; And / or, the binder is selected from polyvinyl alcohol and / or polyethylene glycol.

13. The preparation method according to claim 11 or 12, wherein: In step (1), based on the total weight of the powder, the powder contains: less than or equal to 19.72 wt% of magnesium oxide, less than or equal to 65.71 wt% of aluminum oxide, and 30-99.9 wt% of yttria-stabilized zirconia.

14. The preparation method according to claim 13, wherein: The powder contains: 0.18-16.91wt% of magnesium oxide, 2.15-56.32wt% of aluminum oxide, and 40-97wt% of yttria-stabilized zirconium oxide.

15. The preparation method according to claim 11 or 12, wherein: In step (1), the median particle size of the magnesium oxide is 0.3-1 μm, the median particle size of the aluminum oxide is 0.15-0.6 μm, and the median particle size of the yttria-stabilized zirconia is 0.3-0.6 μm; And / or, the yttria-stabilized zirconia contains 1.5-4 mol% yttria; And / or, the median particle size of the solid phase component in the slurry is 0.3-0.8 μm.

16. The preparation method according to claim 11 or 12, wherein: In step (3), the sintering conditions include: temperature of 1400-1700° C. and time of 1-5 h.

17. The preparation method according to claim 16, wherein: In step (3), the sintering conditions include: temperature of 1450-1650°C; time of 1-2h.

18. A reinforced zirconia ceramic prepared by the method according to any one of claims 11 to 17.

19. An electronic product housing, characterized in that: The electronic product housing contains the reinforced zirconia ceramic according to any one of claims 1-10 and 18.

Citation Information

Patent Citations

  • Magnesium oxide and yttrium oxide stabilized square polycrystal zirconium oxide ceramics and its preparing process

    CN1170787C